Impaired Verbal Memory Recall in Patients With Axonal Degeneration and Serum Glycine-Receptor Autoantibodies—Case Series - Hansen, Niels; Bartels, Claudia; Stöcker, Winfried; Wiltfang, Jens; Fitzner, Dirk (Frontiers in Psychiatry, 2022)
Abstract Background: Glycine receptor antibody-associated neuropsychiatric disease is currently known to be dominated by the phenotypes stiff-person syndrome and progressive encephalomyelitis entailing rigidity and myoclonus. In our case series we aim to depict the less-often reported feature of cognitive impairment associated with glycine receptor antibodies. Methods: We investigated five patients with cognitive impairment varying from mild cognitive impairment to dementia associated with serum glycine receptor antibodies. Mild and major neurocognitive disorders were diagnosed according to the DSM-5 (fifth edition of the Diagnostic and Statistical Manual of Mental Disorders). Neuropsychology via Consortium to Establish a Registry for Alzheimer's Disease (CERAD) testing results, psychopathology data via the Manual for the Assessment and Documentation of Psychopathology in Psychiatry (AMDP), cerebrospinal fluid analysis and magnetic resonance imaging data were retrospectively analyzed from patient files. Results: We identified five patients with cognitive impairment as the main neuropsychiatric feature associated with serum glycine receptor antibodies. One patient also presented akinetic rigidity syndrome. The psychopathology comprised disorders of attention and memory, orientation, formal thought, and affect. In addition to suffering deficits in verbal memory function, figural recall, phonematic fluency, and globally deteriorated cognitive function, these patients presented seriously impaired memory recall in particular. Tau protein and phosphorylated tau protein 181 were elevated in 75% of patients. Conclusions: Our results suggest that axonal neurodegeneration and especially impaired verbal memory recall in addition to deficits in verbal and figural memory characterize patients with progressive cognitive impairment associated with glycine receptor antibodies. This unresolved issue should be clarified by researchers to discover whether axonal degeneration is merely an age-related phenomenon or one related to glycine-receptor autoantibodies in old age. Cognitive impairment as a neuropsychiatric syndrome of glycine-receptor antibody disease is a potential, conceivable, but so far unproven additional feature requiring deeper large-scale investigations and consideration during differential diagnosis in memory clinics.